The Use Of Particles By The Second Semester Students Of English Program at Khairun University - Zulkifli A Badarudin; Jusmin HJ Wahid (Jurnal Ilmiah Wahana Pendidikan, 2019)
The writer applied descriptive method and basic statisic. The data are collected through instruments those are essay test and multiple choice. Essay test is about matching the synonym of the particles and translating the particles into Indonesian language. The data were analyzed and tabulated into rating scale and qualification. Based on the data, the students’ mastery in using particles can be categorized as poor score. This is proven by students’ mean score is 41.77% this is found out that only 3 respondents or 8.57% of them obtained good score 4 resoondents or 11.42% of them obtained sufficient score 10 respondents or 28.57% of them obtained poor score and 18 respondents or 51.42% obtained very poor score. Overall, the second semester students of English study program involved in this research could not use particles correctly